Efektivitas Kunyit (Curcuma longa L.) sebagai Suplemen Pakan Ikan - Rahmadani, Thoy Batun Citra; Diniariwisan, Damai (JURNAL SAINS TEKNOLOGI & LINGKUNGAN, 2024)
Feed supplements for aquaculture activities are materials that currently widely used. There are many feed supplements using herbal ingredients, because it is considered more safety for fish. It is based on prohibition of antibiotics usage, because it can create resistance in microorganisms and has a negative impact on environment. Turmeric is a spice that widely used as a feed supplement. Most turmeric is used for cooking ingredient, but it is also widely used in traditional medicine. Several active compounds in turmeric such as curcumin and turmerone have been studied. These active compound have been proven could increase antioxidant and prevent lipid peroxidation, so it can increase the fish growth. Apart from that, this active compound is also useful in inhibiting bacterial growth by damaging membrane and preventing the formation of biofilms.